Evaluating the Critical Thickness of TiO2 Layer on Insulating Mesoporous Templates for Efficient Current Collection in Dye‐Sensitized Solar Cells. (15th January 2013) - Chandiran, Aravind Kumar; Comte, Pascal; Humphry‐Baker, Robin; Kessler, Florian; Yi, Chenyi; Nazeeruddin, Md. Khaja; Grätzel, Michael
Abstract In this paper, a way of utilizing thin and conformal overlayer of titanium dioxide on an insulating mesoporous template as a photoanode for dye‐sensitized solar cells is presented. Different thicknesses of TiO2 ranging from 1 to 15 nm are deposited on the surface of the template by atomic layer deposition. This systematic study helps unraveling the minimum critical thickness of the TiO2 overlayer required to transport the photogenerated electrons efficiently. A merely 6‐nm‐thick TiO2 film on a 3‐μm mesoporous insulating substrate is shown to transport 8 mA/cm2 of photocurrent density along with ≈900 mV of open‐circuit potential when using our standard donor‐π‐acceptor sensitizer and Co(bipyridine) redox mediator.